Perancangan Buku Cerita Bergambar Legenda Terciptanya Lembah Harau - Qatrun Nada; Ariusmedi Ariusmedi (Jurnal Riset Rumpun Seni, Desain dan Media, 2023)
The illustrated story book The Legend of Harau Valley is a book designed by bringing folklore from Harau. This comic book was created to preserve local folklore and become a medium for introducing folklore to the younger generation. Currently, the younger generation's interest in culture is decreasing, so many people don't know the story about this legend. With this design, it is hoped that the Legend of Harau Valley will be increasingly recognized by the wider community so that it becomes a regional identity and its sustainability is maintained. The illustrations in this design use a semi-realist and full color illustration style to make it more easily accepted and liked by the younger generation. The method used in designing this picture book is the glass box method based on data obtained through observation, interviews, literature studies and documentation of the folklore The Legend of Harau Valley. In the problem solving process, 5W+1H analysis is used. This design resulted in a main media in the form of a picture story book entitled "The Legend of the Creation of the Harau Valley". Supporting media options used are bookmarks, e-books, x-banners, hand fans, mini notebooks, posters and tote bags.